Pengaruh Kebijakan Work from Home Terhadap Kinerja Pegawai di SMK SMAK Padang - Ismaya Indri Astuti; Nasir Nasir (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2021)
The Ministry of Industry of the Republic of Indonesia has taken several regulations connected to Work from Home in response to the President's directions and the Covid-19 outbreak issue. Chemical Analyst Vocational School Padang follows the same guidelines as the Minister of Industry's circular. The Work from Home implementation strategy aims to provide employees with more flexibility by allowing them to work on and complete assignments from home. This researcher wants to know how Work from Home is implemented at Chemical Analyst Vocational School Padang and what the effects of Work from Home policies are on employee performance at Chemical Analyst Vocational School Padang so that they can accurately describe the reality and current conditions in the field. To reduce the hurdles that may arise during Work from Home, Chemical Analyst Vocational School Padang requires good communication and cooperation between employees and their immediate superiors. However, implementing the Work from Home policy has the unintended consequence of increasing staff morale, resulting in more innovative and productive job completion